PKM Peningkatan Kesadaran Dan Pengetahuan Masyarakat Tentang Pencegahan Stunting Melalui Program Edukasi Dan Pendampingan Di Desa Tarikolot - Edi Tohidi; Irfan Ali; Dodi Solihudin; Irena Yulistiano; Muhammad Hagi Badra (CV. Multi Kreasi Media, 2024)
Stunting is a chronic nutritional issue that negatively affects the growth of children in Indonesia. Tarikolot Village faces serious challenges due to the low awareness and knowledge of the community regarding stunting prevention. This Student Creativity Program (PKM) aims to enhance community awareness and knowledge about stunting prevention through education and mentoring activities. The methods employed include socialization, training, and intensive mentoring for pregnant women and families in Tarikolot Village. The results of this program show a significant increase in community knowledge about the importance of balanced nutrition and stunting prevention practices. Thus, this program has successfully contributed to reducing stunting rates in Tarikolot Village.